Reported adverse events during out-of-hospital mechanical ventilation and ventilatory support in emergency medical services and critical care transport crews: a systematic review - Pinto-Villalba, Ricardo Sabastian; Leon-Rojas, Jose E. (Frontiers in Medicine, 2023)
Background Emergency medical services (EMS) and critical care transport crews constantly face critically-ill patients who need ventilatory support in scenarios where correct interventions can be the difference between life and death; furthermore, challenges like limited staff working on the patient and restricted spaces are often present. Due to these, mechanical ventilation (MV) can be a support by liberating staff from managing the airway and allowing them to focus on other areas; however, these patients face many complications that personnel must be aware of. Aims To establish the main complications related to out-of-hospital MV and ventilatory support through a systematic review. Methodology PubMed, BVS and Scopus were searched from inception to July 2021, following the PRISMA guidelines; search strategy and protocol were registered in PROSPERO. Two authors carried out an independent analysis of the articles; any disagreement was solved by mutual consensus, and data was extracted on a pre-determined spreadsheet. Only original articles were included, and risk of bias was assessed with quality assessment tools from the National Institutes of Health. Results The literature search yielded a total of 2,260 articles, of which 26 were included in the systematic review, with a total of 9,418 patients with out-of-hospital MV; 56.1% were male, and the age ranged from 18 to 82 years. In general terms of aetiology, 12.2% of ventilatory problems were traumatic in origin, and 64.8% were non-traumatic, with slight changes between out-of-hospital settings. Mechanical ventilation was performed 49.2% of the time in prehospital settings and 50.8% of the time in interfacility transport settings (IFTS). Invasive mechanical ventilation was used 98.8% of the time in IFTS while non-invasive ventilation was used 96.7% of the time in prehospital settings. Reporting of adverse events occurred in 9.1% of cases, of which 94.4% were critical events, mainly pneumothorax in 33.1% of cases and hypotension in 27.6% of cases, with important considerations between type of out-of-hospital setting and ventilatory mode; total mortality was 8.4%. Conclusion Reported adverse events of out-of-hospital mechanical ventilation vary between settings and ventilatory modes; this knowledge could aid EMS providers in promptly recognizing and resolving such clinical situations, depending on the type of scenario being faced.